Avoiding Abdominal Flank Bulge after Lumbotomy Incision: Cadaveric Study and Ultrasonographic Investigation - Ozel, L.; Marur, T.; Unal, E.; Kara, M.; Erdogdu, E.; Demir, T.; Berber, I.; Gurkan, A.; Kilicoglu, G.; Bakal, N.; Titiz, M. I. (ELSEVIER SCIENCE INC, 2012)
8th Congress of the Turkish-Transplantation-Centers-Coordination-Association (TTCCA), Antalya, TURKEY, OCT 12-16, 2011